Colonial Impotence Virtue and Violence in a Congolese Concession (1911-1940) - Henriet, Benoît (Africa in Global History, 2021)
This book offers a historical anthropology of the Leverville concession, the largest palm oil exploitation in Belgian Congo, and one of Unilever's main plants outside of Europe, between 1911 and 1940. It provides new understandings of the joint experience of colonialism and capitalism. As a focused case study this book offers a unique take on the global history of the early 20th century.